Duolingo As a Digital Tool for Enhancing English As a Foreign Language (EFL) Speaking Proficiency at Zain Academy - Khomariyah, Yanti; Ekowijayanto, Mochlis (RIGGS: Journal of Artificial Intelligence and Digital Business, 2025)
This study aims to explore the integration of the Duolingo application into English speaking instruction for English as a Foreign Language (EFL) students at Zain Academy within a blended learning framework. Employing a descriptive qualitative approach, data were collected through interviews, observations, and documentation, then analyzed thematically. The findings reveal that Duolingo positively contributes to four key areas of speaking proficiency: building students' confidence, improving pronunciation, enhancing vocabulary acquisition, and strengthening basic sentence construction. The app's adaptive, multimodal, and gamified design facilitates linguistic development in an engaging and accessible manner. Nevertheless, the study also identifies several limitations, such as the lack of real-time interaction, difficulty in mastering complex sentence structures, and declining motivation during extended use. Within a blended learning environment, Duolingo proves more effective when complemented by classroom-based speaking practice and guided teacher feedback. Thus, the synergy between technological tools and pedagogical intervention becomes essential in maximizing the effectiveness of app-based language learning. The study recommends Duolingo as a supportive tool within hybrid learning strategies that is flexible, measurable, and oriented toward authentic communication development.